Konsep Gad al-Basar Menurut Tafsir Al-Maragi dan Relevansinya dengan Pendidikan Agama Islam - Aisyatur Rosyidah (FAI, 2017)
Konsep Gad al-Basar Menurut Tafsir Al-Maragi dan Relevansinya dengan Pendidikan Agama Islam